Caracterização e análise do talude continental adjacente à bacia potiguar, NE Brasil - Almeida, Narelle Maia de (2014)
This work presents the results of the first imaging of continental slope adjacent to Potiguar Basin, in the equatorial Brazilian margin (NE Brazil). Swath bathymetry provided a complete coverage of seafloor between the upper and middle slope (100-1,300 m). Fifteen submarine canyons were mapped. The shape of the slope reflects in distinct spatial distribution of the canyons. The western area displays convex profiles which implied a greater amount of incisions by canyons. Some of them have gradient walls higher than 35°. They were classified according to location and morphology. The canyons with heads indenting shelf edge, association with a incised valley and a large fluvial system, high sinuosities, V shape, terraces along margins, further erosive features such as landslide and gullies allow to deduce a sandy-gravelly sedimentation. These canyons are associated with deposition of submarine fan systems that have been considered permeable hydrocarbon reservoirs. The presence of gullies, furrows and dunes demonstrates the role of bottom currents in the shaping of the slope. The enlargement of canyons and the change in the course when they cross the border fault imply that tectonic has also influenced in the morphology of deep waters environments of Potiguar Basin. The current sedimentation of continental slope is considered mixed because the sediments are composed of siliciclastics and bioclasts. Predominant siliciclastics are calcite, dolomite, quartz, and clay minerals. The presence of stable minerals (zircon, tourmaline and rutile), and fragmented bioclasts implies the contributions of Rivers Açu and Apodi